MENGURANGI PRODUK RETURN DENGAN METODE QUALITY CONTROL CIRCLE DAN QUALITY LOSS FUNCTION DI DEPARTMENT OFFSET PACKAGING PT. IKPP SERANG - Wirawati, Sri Mukti; Syarifudin, Achmad; Eko Fauzie (AGUSPATI Research Institute, 2022)
Increased returns from Shinzui's folding box goods, which had various flaws, cost the offset packaging department money. The goal of this research is to assess the losses incurred and to provide a solution to the problem of returned items or returned goods from consumers, which has been more prevalent in recent months. The advantages of research include being able to determine the losses incurred and finding effective techniques to lessen the return of items. The quality loss function technique is used to determine how much loss has occurred, and the quality control circle method is also used to determine the origin of the problem using a qualitative way and then conduct an analysis to make immediate adjustments. The outcomes of. Keywords : Returning product, Quality control circle, Quality loss function